PERLINDUNGAN HUKUM TERHADAP KELOMPOK AGAMA MINORITAS DALAM HUKUM PIDANA INDONESIA - Sumika Putri, Nella (Faculty of Law, Parahyangan Catholic University, 2018)
Criminal law should provide protection to all citizens (individually or communities) without regard to their ethnicity, race or religion. In addition, it is also important that its implementation should be done non-discriminatively. This research is done using a normative juridical approach. The most important finding is that a number of penal regulations (inter alia, prohibiting blasphemy, genocide or in the criminal code draft relating to extra-marital sex) in its implementation and enforcement results in discrimination or even worse persecution of minority groups. The author here argues that, in order to guarantee the principle of equal treatment before the law and protection of (religious) minority groups, those penal regulations should be harmonized and read within the context of other existing penal rules.